Analisis Potensi Pemanfaatan Energi Angin Sebagai Sumber Energi Listrik Di Indonesia - Lathifah, Harirotul; ., Sudarti; ., Yushardi (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This research was carried out in order to find out the potential for utilizing wind energy as a source of electrical energy in Indonesia. Where this research is to fulfill the final assignment of the environmental physics course. This research is a literature study which aims to analyze several results of articles, journals and previous research. The purpose of this analysis refers to the application and development of the potential use of wind energy as a source of electrical energy in various regions of Indonesia. Like in the rice fields of Blang Krueng Village, Baitussalam District. This research is a qualitative descriptive design method through analysis, identification and exploration of previous findings. The subject targeted for this research is the use of wind energy as a source of electrical energy in various regions of Indonesia. The objects of this research are journals and articles. Briefly, the results of this research show two categories. first analysis of the categories of application of wind energy as a source of electrical energy in various regions of Indonesia. Analysis of the two categories of authentic development from several researchers who developed hydropower as a source of electrical energy.